The Challenge of Islamic Education and How to Change - Dodi Ilham (International Journal of Asian Education, 2020)
The realignment of the Islamic education system is not just modification or patchwork. Still, it requires reconstruction, reconciliation, and reorientation so that Islamic education can make a significant contribution to the achievement of the take-off stage. In this paper, the author tries to offer several solutive arguments as well as to become a plan for Islamic education. First, it needs a review of the Islamic education system that is currently running while still promoting the spirit of Islamic teachings. The vision is manifest in the form of an attempt to re-dialogue religious texts against every reality that occurs. Second, prepare more mature and quality human resources armed with comprehensive capabilities. Third, reaffirming the role of all elements in education, namely, individuals, families, communities, educational institutions, and the state. Fourth, to unite Islamic spirituality with science and technology as a strong basis for increasingly pressing challenges, Islamic intellectual tradition, is a hierarchy and interconnection between various scientific disciplines that enable the realization of unity (oneness) in diversity, not just in the realm of faith and religious experience, but also in the world of knowledge.